Shear strength of cemented sand gravel and rock materials - Liu, Zhongwei; Jia, JinSheng; Feng, Wei; Ma, Fengling; Zheng, Cuiying (Penerbit Universiti Kebangsaan Malaysia, 2017)
Shear strength is currently a significant parameter in the design of cemented sand gravel and rock (CSGR) dams. Shear strength tests were carried out to compare material without layers noumenon and layer condition. The experimental results showed good linearity in the curves of shear strength and pure grinding tests with correlation coefficients of nearly 97%. The friction coefficient was similar to that of C10 roller-compacted concrete (RCC), but the cohesion value was weaker than that of RCC. The shear strength of the CSGR layers decreased by 40% when retarding mixtures were not added and the layer was paved immediately after 4 h of waiting interval.